Exploratory Factor and Reliability Analysis of Financial Literacy Instrument to Assess Low-Income Groups in Malaysia - Munisamy, Ananthan; Sahid, Sheerad; Hussin, Muhammad (Journal of Social Economics Research, 2022)
Financial literacy (FL) helps individuals make more assertive and efficient financial decisions. However, there is limited knowledge regarding the dimensions of FL as pertaining to low-income or Bottom 40% (B40) households in Malaysia. Therefore, the present study examined the reliability and validity of the B40 financial literacy measurement scale. A self-administered survey questionnaire was employed. The sample consisted of 100 respondents randomly selected from B40 households in Johor, Malaysia. The analysis was carried out through Exploratory Factor Analysis (EFA) via IBM-SPSS version 22.0 software. To measure the FL constructs, the study initially developed 59 items; however, six items were deleted as the factor loading was below the 0.50 cut-off point, while 53 items were retained as their factor loading was more than 0.50. Because the study validates the dimension that leads to improved FL, the findings are particularly beneficial to Malaysian B40 households who have been identified as the most vulnerable group; the findings will help action to be taken to improve the FL levels of B40 households.